Profil Kemampuan Berpikir Kreatif dan Komunikasi Ilmiah Siswa SMP pada Materi Teknologi Ramah Lingkungan - Dine Nurdian; Saefudin; Amprasto (Postgraduate, University of Mataram, 2023)
Students' creative thinking and scientific communication skills are needed by students so they can compete healthily and be able to solve various increasingly complex problems in the 21st century. This research aims to determine the profile of student's creative thinking and scientific communication abilities in learning environmentally friendly technology. The method used in this research is quantitative descriptive. The research sample consisted of 35 students, 16 men and 19 women. The instrument used is an essay test on environmentally friendly technology material. For creative thinking skills, indicators for fluent thinking, flexible thinking, original thinking, and the ability to elaborate are used, while for scientific communication indicators for representing knowledge are used. From the results of data analysis, it show that only 1 student (3%) has creative thinking abilities in the high category, 21 students (60%) in the medium category, and 13 students (37%) in the very low category. Students' scientific communication skills for indicators represent 4 students in the very high category (11.4%), 2 students in the high category (5.7%), 10 students in the medium category (28.6%), and 2 students in the low category. (5.7%), and 17 students (48.6%) in the very low category. So students' overall creative thinking and scientific communication abilities must be improved.